Evaluation of Microbial Numbers and Physical Properties of Milk Preserved with Different Time of Pre-Heating and Pulsed Electric Fields (PEF) Exposure - Anugerah Dany Priyanto; Teti Estiasih; Angky Wahyu Putranto; Widyasari Widyasari; Rahmawati Rahmawati (Faculty of Animal Science Universitas Brawijaya, 2022)
Milk production is intended for human consumption; hence preservation technology is required while maintaining the sensory and nutritional attributes. Some of technologies applied in milk are the use of pre-heating combined with pulsed electric fields (PEF) exposure. The aim of this study was to examine the effect of combination food preservation techniques using pre-heating and PEF with various conditions. The raw milk first received the pre-heating treatment at 70 ËšC, followed by PEF exposure. A completely randomized design (CDR) was applied in this research. It used two factors, namely factor I (pre-heating duration: 10, 20, and 30 minutes), and factor II (PEF exposure duration: 2, 4, and 6 minutes) with three replications, resulting in nine (9) treatments. The results reveal that there was a bacterial reduction within the range of 0.70-1.06 log CFU/mL. Besides, the increasing duration of pre-heating combined with PEF exposure decrease the values of viscosity, emulsion stability, and lightness of raw milk samples. Moreover, the most effective treatment observed in the raw milk-treated with pre-heating of 10 minutes and PEF of 2 minutes, with the level of TPC, viscosity, emulsion stability, and lightness of 1.88 log CFU/mL, 14.65 cP, and 95.65%, respectively